Patients With LR-HPV Infection Have a Distinct Vaginal Microbiota in Comparison With Healthy Controls - Zhou, Yunying; Wang, Lu; Pei, Fengyan; Ji, Mingyu; Zhang, Fang; Sun, Yingshuo; Zhao, Qianqian; Hong, Yatian; Wang, Xiao; Tian, Juanjuan; Wang, Yunshan (Frontiers in Cellular and Infection Microbiology, 2019)
Condyloma acuminatum (CA) is a benign epithelium hyperplasia mainly caused by human papillomavirus (HPV) which has already occupied the second most common viral sexually transmitted infections (STIs) in China. 90% of CA patients are caused by the low-risk HPV 6 and 11. Except low-risk HPV infection there are likely other factors within the local microenvironment that contribute to CA and there has related articles so far. In this study, 62 vaginal specimens were analyzed using 16S rRNA gene sequencing. The diversity of the vaginal microbiota was higher and the composition was different with LR-HPV infection. While the relative abundance of dominant Firmicutes was lower, Actinobacteria, Proteobacteria and Fusobacteria phyla were significantly higher; at the genus level Gardnerella, Bifidobacterium, Sneathia, Hydrogenophilus, Burkholderia and Atopobium were higher. This study firstly confirmed a more accurate and comprehensive understanding of the relationship between low-risk HPV infection and vaginal microbiota, in order to provide a theoretical basis for further research on the occurrence and development of CA. Keywords: Low-risk HPV, Condyloma acuminatum, vaginal microbiome, 16S rRNA sequencing